What Happens If We Start from Nigeria? Diversifying Histories of Geography. Issue 3 (3rd May 2020) - Craggs, Ruth; Neate, Hannah
Abstract : This article asks this question: What if, rather than starting from the United States or the United Kingdom in histories of geography, we start from Nigeria? Focusing on Nigerian geographers working in Nigeria's first university from 1948 to 1990 and drawing on archival evidence and new oral history interviews, this article argues that the view from Nigeria offers significant new perspectives on the history of geography. First, it highlights the intellectual contribution of Nigerian scholars, illustrating the partial and exclusionary nature of many traditional histories. Second, it illuminates the as yet unacknowledged impact of the Cold War on the discipline far beyond the United States and Soviet Union. Third, this new perspective makes it possible to consider afresh the contemporary Anglo-American hegemony of international geography, providing evidence of the consequences of this hegemony for scholars working beyond the West and revealing the less hierarchical alternatives that at some moments appeared possible. Fourth, by highlighting the shifting structures that facilitated and foreclosed opportunities for participation in the international geographical community, the article provides an original insight into the conditions of academic labor and considers the crucial question of what, for the work of constructing a more equal academic community in the future, we might learn from this earlier period. Key Words: academic labor, Anglo-American hegemony, Cold War, decolonization, history of geography, Nigeria.